AB0132 Prevalence of Soluble PAD4 and Anti-PAD4 Antibodies in Autoimmune Diseases- Association to Several Acpas but Not to Shared Epitopes in Patients with Rheumatoid Arthritis. (9th June 2015) - Umeda, N.; Matsumoto, I.; Kondo, Y.; Tsuboi, H.; Kagami, Y.; Ishigami, A.; Maruyama, N.; Sumida, T.
Abstract : Background: Anti-citrullinated proteins/peptides antibodies (ACPAs) are major predictor of disease severity of patients with rheumatoid arthritis (RA). Citrullination is the post-translational modification mediated by peptidylarginine deiminases (PADs). PAD4, one of the PAD isozyme, is expressed in granulocytes and monocytes, as well as in the synovial lining cells of RA synovium. However, the specificity and prevalence of plasma PAD4 and anti-PAD4 antibodies (Abs) have not yet to be defined. Further, association of PAD4 and anti-PAD4 with ACPAs, HLA-DRB1 shared epitope (SE) alleles and disease activity were not clear. Objectives: To investigate the prevalence of PAD4 and anti-PAD4 Abs in autoimmune diseases and to clarify their association with ACPAs, SE and disease activity in patients with RA. Methods: Levels of human PAD4 and anti-PAD4 Abs in serum or plasma were measured by sandwich ELISA. Samples were obtained from patients with RA (n=48), systemic lupus erythematosus (SLE; n=36), or Sjögren's syndrome (SS; n=37) and from healthy controls (HC; n=40). Antibodies against cyclic citrullinated glucose-6-phosphate isomerase (CCG)-2, -7, anti-citrullinated alpha enolase-1 (CEP-1), and anti-CCP Abs were also measured by ELISA. Patients with RA were genotyped for HLA-DRB1. The levels of human PAD4 and anti-PAD4 Abs were compared with the levels of ACPAs and SE alleles in patients with RA. Results: The mean levels of PAD4 were 111.9 U/ml in patients with RA, 30.4 U/ml in SLE, 81.9 U/ml in SS, and 46.6 U/ml in HC. The PAD4 levels were significantly higher in RA than in SLE or HC (P<0.01). Anti-PAD4 Abs were detected in 44 of the 148 patients with RA (29.7%), but not in patients with SLE or SS and in the HC. In RA patients, the PAD4 levels in the anti-PAD4-negative group were significantly higher than those in the anti-PAD4-positive group. Moreover, the anti-CCG-2, -7, CEP-1, and anti-CCP Ab levels were significantly higher in the anti-PAD4-positive group than in the anti-PAD4-negative group. In RA patients, the PAD4 levels were not correlated with the anti-CCG-2, -7, CEP-1, or CCP Abs, and with the CRP, ESR, RF, MMP-3, IgG, or DAS28-CRP levels. Neither PAD4 nor anti-PAD4 Abs were statistically correlated with the presence of SE alleles. Conclusions: PAD4 levels were higher in RA patients than in SLE patients or HC. Anti-PAD4 Abs appeared specifically in patients with RA and were associated with ACPA levels but not with SE. Disclosure of Interest: None declared